Multi-source Image Fusion Technology in Different Fields of View - Si Tian; Junju Zhang; Yihui Yuan; Benkang Chang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
There exist a lot of image systems of different features in different field of view (FOV) in our real life. Multi-source fusion technology in different FOV is able to promote the performance of image acquisition system without additional investment in hardware equipment. With regards to multi-image fusion technology in different FOV, in this research a registration method combined with affine transformation and linear interpolation is proposed, which analyzes pre- and post- fused images from the temporal and spatial perspective for comparison, evaluates and compares the fusion result so as to testify the applicable feasibility of the technology. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3229